2021
DOI: 10.1108/sbr-07-2020-0096
|View full text |Cite
|
Sign up to set email alerts
|

Do education sector credit cards differ with other credit cards in Malaysia?

Abstract: Purpose The credit card market is very large and segmented by targeting different types of consumers. One type of credit card is one that specifically targets people in the education sector, for instance, students, teachers and other staff members. This study aims to compare the features of education and other credit cards in Malaysia. Design/methodology/approach The study analyzes data concerning 234 credit cards by using descriptive statistics and a one-way analysis of variance test. Findings Out of 234 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Study on the employees of Malaysian institution of higher learning shoed a positive attitude about using credit cards [11]. Though study showed that the education related credit cards are statistically significantly different from other types of credit cards in Malaysia only for two features: interest rate and cash withdrawal charge fees [6], college students showed positive attitudes about cognitive variables [15]. Affective credit attitude influenced credit card purchase behaviour among college students [16].…”
Section: Literature Reiviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Study on the employees of Malaysian institution of higher learning shoed a positive attitude about using credit cards [11]. Though study showed that the education related credit cards are statistically significantly different from other types of credit cards in Malaysia only for two features: interest rate and cash withdrawal charge fees [6], college students showed positive attitudes about cognitive variables [15]. Affective credit attitude influenced credit card purchase behaviour among college students [16].…”
Section: Literature Reiviewmentioning
confidence: 99%
“…In both the Islamic and conventional bank systems, credit cards in Malaysia can be classified as standard, gold, or platinum based on their objectives and consumer categories [6,7,8]. Classic credit cards are offered to customers with steady earnings and low credit scores, whereas gold cards are offered to those with a high income and a good credit score.…”
Section: Introductionmentioning
confidence: 99%
“…Malaysian credit card sales have been gradually increasing over time since the introduction in 1970s (Kang & Ma, 2007;Nazimah, 2011;Jusoh & Lim, 2012;Siti, Salin, & NurAien, 2013;Alam, Ibrahim, & Sriyana, 2021). The credit line for credit cards was increased to RM125 billion in 2012, with 325 million trades reported.…”
Section: Introductionmentioning
confidence: 99%